2018
DOI: 10.3390/en11020304
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Tensile Strength of Anisotropic Rocks: Review and New Insights

Abstract: Strength anisotropy is one of the most distinct features of anisotropic rocks, and it also normally reveals strong anisotropy in Brazilian test Strength ("BtS"). Theoretical research on the "BtS" of anisotropic rocks is seldom performed, and in particular some significant factors, such as the anisotropic tensile strength of anisotropic rocks, the initial Brazilian disc fracture points, and the stress distribution on the Brazilian disc, are often ignored. The aim of the present paper is to review the state of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Anisotropic rocks exhibit different properties in different directions. Several experimental studies ( [22][23][24][31][32][33][34][35][36][37][38][39][40][41]) indicate that the majority of sedimentary and metamorphic rocks are affected by strength anisotropy related to discontinuities. The results of triaxial tests and direct and indirect tensile tests carried out on these rocks show that strength changes with loading orientation.…”
Section: Selection Of Strength Criteria For Rocks With Strength Anisomentioning
confidence: 99%
See 4 more Smart Citations
“…Anisotropic rocks exhibit different properties in different directions. Several experimental studies ( [22][23][24][31][32][33][34][35][36][37][38][39][40][41]) indicate that the majority of sedimentary and metamorphic rocks are affected by strength anisotropy related to discontinuities. The results of triaxial tests and direct and indirect tensile tests carried out on these rocks show that strength changes with loading orientation.…”
Section: Selection Of Strength Criteria For Rocks With Strength Anisomentioning
confidence: 99%
“…However, the failure pattern in these rocks is quite complex. A review of Brazilian tests on anisotropic rocks performed by Ma et al [24] indicated that 5 types of failure can occur: tensile failure across the weakness planes; tensile failure along the weakness planes; shear failure across the weakness planes; shear failure along the weakness planes; and mixed failure.…”
Section: The Nova and Zaninetti Criterionmentioning
confidence: 99%
See 3 more Smart Citations